Fast calculation of the maximum power point of photovoltaic generators under partial shading (2016)
This paper presents a method to calculate the energy production of photovoltaic generators considering partial shading or mismatched conditions. The proposed method is based on the complete one-diode model including the bypass diode in its exponential form, where the current and voltage values of the modules composing the photovoltaic panel array are calculated without using the Lambert-W function. In addition, the method introduces a procedure to calculate the vicinity of the maximum power points, which enables the reduction of the operations required to obtain the global maximum. The proposed method provides short simulation times and high accuracy. On the other hand, since the method does not require complex mathematical functions, it can be implemented straightforwardly on known software packages and development languages such as C and C++. Those characteristics make this method a useful tool to evaluate the economic viability and return-of-investment time of photovoltaic installations. Simulation results and comparisons with a classical procedure confirm the good performance of the proposed method in terms of execution time and accuracy.